Epidemiologic and Clinical Characteristics of Children with Measles during the Year 2019 - Adnan H. Aljothery 1 , Hasan Alwan Baiee 2 , Kassim Fakhir Hussein3 , Ameer Hasan Baiee 4 , Taif Sal (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Measles remains a major public health problem in many developing countries including Iraq, Objective: To describe the epidemiological and clinical profiles of measles among children admitted to Babylon Teaching Hospital for Maternity and Children . Methodology : A descriptive observational cross sectional epidemiologic study was conducted on children diagnosed and admitted to Babylon teaching hospital for Maternity and Children . using the (person, place, time epidemiological model ) during the period from 1st of January 2019 to the 1st of September 2019. The total number patients was 157. The independent variables studied include; age, gender, residence, time of admission, nutritional status, vaccination status, any co morbidities, clinical presentations and complications. Results : One hundred fifty seven clinically and serologically diagnosed measles cases who were admitted to Babylon Teaching Hospital for Maternity and Children . . The male to female ratio was 1.4: 1 the mean age of the patients 35.15±38.5 months(ranging between one month to 11 years). In this study Children under years were most affected. Seventy four percent patients were from rural districts and sub districts. The disease took the profile of epidemic and was seen most often during the hot season, with a peak in July. Majority of cases stayed in the hospital for three days and more. Only one death was reported with a a case fatality rate ( 0.63%).The most common complications in this study was pneumonia. Conclusion: Measles remains a common, endemic illness mostly due to inadequate vaccination coverage, further analytic studies are strongly requested in Iraq to identify the real potential risk factors of the occurrence of this serious endemic diseases.